Pemanfaatan Lahan Pekarangan Bagi Kelompok Wanita Tani (KWT) Srikandi Kelurahan Bentiring Permai, Kota Bengkulu - Puspita Sari, Anjelia; Rohim, Ahmad; Agustus , Rahmat Fajar; Alvio, Liwan (Indra Institute Research & Publication, 2024)
Empowering KWTs in utilizing yard land is one way to fulfill needs without having to buy it. The yard around the house can be a place for farming activities which have a big role in meeting family needs. Yards are basically used for various purpose.goals, for example as a living dispensary, increasing family income. However, limited knowledge of vegetable cultivation is an obstacle in the vegetable production process. So there is a need for training on the use of yard land at KWT Srikandi. Therefore, the aim of this activity is to increase the knowledge and insight of KWT women in cultivating their yard with various vegetable plants and kitchen spices which can provide additional income for the family. The method used is the lecture method and direct training with several stages, namely preparation, counseling, training and mentoring. Efforts to utilize homestead land have had a good impact on the farmer groups of Bentiring Permai subdistrict.